Characterization of limestone and dolomite using x-ray fluorescent (XRF) for cement processing - Mokhzani Khair, Ishak; Khairul Nizar, Ismail; Kamarudin, Hussin; Wan Mohd Sabki, Wan Omar; Banjuraizah, Johar; Mohd Nazry, Salleh; Umar, Kassim (Mineral Research Centre, 2011)
Mineral Symposium 2009 (SIMPOMIN 2009) organized by Mineral Research Centre, from 9th - 11th November 2009 at Bukit Merah Laketown Resort, Perak.